Analisis Gerak Silek Pauh Di Perguruan Silaturrahmi Kelurahan Kalumbuk Kecamatan Kuranji Kota Padang - Roja’atul Khoiriyah; Desfiarni Desfiarni (Institut Nalanda, 2023)
The purpose of this study is to describe and analyze the Silek Pauh movement in Kalumbuk Village Friendship College, Padang City, Kuranji District from the perspective of space, time and energy. This research uses qualitative research with descriptive and analytical methods. This research instrument is the researcher himself and is assisted by supporting devices such as stationery, cameras and mobile phones. Daat is collected through literature study, observation, interviews and documentation. The stages of data analysis are data collection, data reduction, data modeling and data collection. The results showed that Silek Pauh has motion analysis based on space, time and energy. This can be seen in the well-constructed movements. Pauh's smooth motion mostly forms curved lines in relation to space, meaning a light, dynamic, and powerful figure. In the time aspect, Silek Pauh's movements follow the musical accompaniment played by the musician. The aspect of Silek Pauh's movement time in the results of this study is more dominant using the tempo being carried out by the martial artist. In the power aspect, it uses a lot of and medium power because the movement uses the attraction of fights between attackers and detractors using the property of a cleaver (knife).